Walkability pada Jalur Pedestrian di Area Universitas Negeri Malang - shahnez paramastri; Sigmawan Tri Pamungkas (Jurnal Mahasiswa Jurusan Arsitektur, 2018)
Malang State University (UM) have design to be the green campus, there is an university haveattention about campus area condition and campus with personality showed by the campus areacondition. Campus with personality care about campus area condition can be created by mixingsocial element and nature element. But, since the program green campus have started, there is nota single observation or research about walkabilty in pedestrian path, this mean to maximizefunction of pedestrian path for support green campus Program. Objective of this research isknowing walkability level in studies location, the result will be evaluation report and reference forplainning in future. In this research using mixed method or qualitative method and quantitativemethod. Qualitative method used to measure assesment researcher and pedestrian paerceptionabout walkability of pedestrian path in studies location basic from US Department Health andHuman Service standard. Result from the research showing that Malang State Universityclassified as walkable enough for pedestrian path that score obtained 46. But there still muchaspect about pedestrian path walkability have to upgrading because less than standard. Forexcample sidewalk, pedestrian conflict, street furniture, accessbility for difabel and aestheticssmust be to fixed. The result of this research can use by goverment or planology for urban design torealize walkable campus and attract students to walk.